Maxillary Sinus Floor Augmentation With or Without Barrier Membrane Coverage of the Lateral Window: a Systematic Review and Meta-Analysis - Thomas Starch-Jensen; Daniel Deluiz; Kirsten Duch; Eduardo Muniz Barretto Tinoco (eJournal of Oral Maxillofacial Research)
Objectives: Test the hypothesis of no difference in implant treatment outcomes after maxillary sinus floor augmentation with or without barrier membrane coverage of the lateral window.